Evaluation of Heavy Metals Content, Mutagenicity, and Sterility of Indonesian Coral Goniopora sp. as Bone Graft Candidate - Chotimah, Chusnul; Latief, Benny S.; Kartasasmita, Rahmana E.; Wibowo, Marlia S.; Santoso, Muhayatun (Journal of Mathematical and Fundamental Sciences, 2013)
It has been reported that Goniopora sp. coral originating from sea water can induce osteogenesis and regeneration of bone. However, biocompatibility and safety aspects of this material have not been reported yet. We have evaluated the mutagenicity of the raw material and the sterility of processed material of Indonesian coral Goniopora sp. as a potential candidate for osteogenic bone graft. In addition, heavy metals were also identified and determined. A mutagenicity test was conducted using the Ames test, while a sterility test was carried out based on the direct inoculation method. The heavy metals tested "“ including arsenic, lead, cadmium, chrome, cobalt, silver, and mercury "“ were analyzed by neutron activation analysis or atomic absorption spectrophotometry. The results showed that the Indonesian coral did not display mutagenic properties and proved sterile after irradiation. Arsenic, lead, cadmium, mercury, chrome, cobalt, and silver were identified at a concentration level of â‰¤ 2.65, â‰¤3.60, 25.23, 1.72, 34.67, 0.51, and 44.01 ppm, respectively. Taking into account arsenic, lead, cadmium and mercury contents and their provisional tolerable daily intake (PTDI) values, the maximum daily safe exposure level of Indonesian coral Goniopora sp. was predicted to be 1 g/person. It was concluded that the coral can be developed as a potential osteogenic bone graft.